1990
DOI: 10.1126/science.2144364
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation by Wild-Type but Not Transforming Mutants of the p53 Anti-Oncogene

Abstract: The protein encoded by the wild-type p53 proto-oncogene has been shown to suppress transformation, whereas certain mutations that alter p53 become transformation competent. Fusion proteins between p53 and the GAL4 DNA binding domain were made to anchor p53 to a DNA target sequence and to allow measurement of transcriptional activation of a reporter plasmid. The wildtype p53 stimulated transcription in this assay, but two transforming mutations in p53 were unable to act as transcriptional activators. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
331
0
4

Year Published

1994
1994
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(339 citation statements)
references
References 34 publications
4
331
0
4
Order By: Relevance
“…First, it was reported that p53 contained an acidic domain near its N-terminus resembling those previously described in well-characterized transcription factors. By using hybrid proteins containing the DNA binding domain of yeast GAL4 and portions of p53 (Fields and Jang, 1990;Raycroft et al, 1990), it was shown that p53 protein contained a transcriptionactivating sequence that functions in both yeast and mammalian cells. The NH2-terminal 73 residues of p53 activated transcription as e ciently as the herpes virus protein VP16 which contains one of the strongest known activation domain.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…First, it was reported that p53 contained an acidic domain near its N-terminus resembling those previously described in well-characterized transcription factors. By using hybrid proteins containing the DNA binding domain of yeast GAL4 and portions of p53 (Fields and Jang, 1990;Raycroft et al, 1990), it was shown that p53 protein contained a transcriptionactivating sequence that functions in both yeast and mammalian cells. The NH2-terminal 73 residues of p53 activated transcription as e ciently as the herpes virus protein VP16 which contains one of the strongest known activation domain.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…It was demonstrated that p53 could function as a transcription factor (Field and Jang, 1990;Raycroft et al, 1990) and the mdm2 gene is one of its targets (Barak et al, 1993;Momand et al, 1992;Oliner et al, 1993). It is argued that mdm2 is also a critical cellular inhibitor of p53 function as mdm2 knock out mice are embryonic lethal but this is rescued in a p53 null background (de Oca Luna et al, 1995;Jones et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The amino-terminal region of p53 is acidic and proline-rich, and holds the transcriptional transactivation function of the protein (Fields and Jang, 1990;Raycroft et al, 1990). This region has been shown to interact with the components of the basal transcriptional machinery TATA-binding proteins (TBP) (Seto et al, 1992), the TBP associated coactivator factors TAFII40, TAFII60 (Thut et al, 1995), TAFII31 (Lu and Levine, 1995) and members of the transcriptional coactivators p300/CBP family (Gu et al, 1997;Lill et al, 1997).…”
Section: Introductionmentioning
confidence: 99%